Correlation between sunspot magnetic fields and near-ground temperature - Lozitska, N.I. (Кинематика и физика небесных тел, 2005)
The data on measurements of sunspot magnetic fields Bsp and near-ground temperature T on the Earth from 1924 to 2004 are analysed. A reliable positive correlation between these parameters is found. The correlation is stronger at high geographical latitudes, for example, for latitudes of 65° N and 80° N the correlation coefficients r are 0.5 and 0.6, respectively (p < 0.01). It is significant that for the same time interval the correlation between the Wolf number W and T is weaker, r = 0.2, p < 0.05. These results indicate that global warming of the Earth’s climate which has been observed since about 1965 can be connected with long-term changes of solar magnetism.